Corn Grain Weight: Dependence upon Nitrogen Supply and Source-Sink Relations - J. A. Fernandez; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2021)
From a yield component perspective, final grain yield in corn (Zea maysL.) is the result of the number of grains per unit area and their final grain weight. The understanding of grain weight parameters, the rate and duration of grain growth, is critical to improve our rational design of management practices and breeding strategies. In this study, we attempted to determine the effect on grain weight and grain-filling parameters of source-sink modifications (i.e. the amount of assimilates available per grain) during linear grain fill under contrasting levels of nitrogen (N) fertilization in two commercially available US corn hybrids. Two hybrids (3394 and P1197) were evaluated under zero-N and two fertilized strategies at a N rate of 194 lb/a. Four levels of source-sink manipulations were implemented: 1) control; 2) reduced sink, with partially restricted pollination; 3) reduced source, with partial defoliation; and 4) both reduced sink and source. Final grain weight was significantly affected by N management and by modifications of the source-sink ratio during grain-filling. In addition, variations in grain filling rate were responsible for the major changes in grain weight. Results from this study suggest that grain weight is very responsive to reductions in the source capacity during grain-filling, but only marginally responsive to increments in the assimilate availability per seed during grain-filling.
Keywords: maize; Zea mays L.; kernel weight; nitrogen; grain filling; dry-down